Permeability of untreated and atmospheric plasma treated coconut fiber mats - De Oliveira, Daniel Magalhães [UNESP]; De Carvalho Benini, Kelly Cristina Coelho [UNESP]; Monticeli, Francisco MacIel [UNESP]; Schukraft, Joél Pascal [UNESP]; De Bomfim, Anne Shayene Campos [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (IOP Publishing, 2019)
Composites manufactured by resin transfer molding depend on appropriate processing parameters to ensure adequate reinforcement-matrix adhesion. Permeability predicts the fluid flow resistance through reinforcement. The purpose of this work is to evaluate the influence of atmospheric plasma treatment on the permeability of coconut fiber mats. Glycerin solution simulated matrix impregnation of untreated and treated mats. Data from scanning electron microscopy and a decrease in contact angle from 96° to 61° for treated fibers explained the difference in permeability due to etching phenomenon that caused a decrease in permeability value. Kozeny-Carman ratified changes in the permeability of coconut fiber mats. Atmospheric plasma treatment turns fibers more hydrophilic enabling better fluid impregnation in addition to a more regular and slower flow front.
Keywords: Adhesion; coconut fibers; permeability; plasma treatment; resin transfer molding